With Light Steam : A Personal Journey through the Russian Baths - MacWilliams, Bryon (Book collections on Project MUSE., 2014)
In 1996 Bryon MacWilliams left the relative stability of the United States for the chaos of post-Soviet Russia and stayed. Over the course of nearly twelve years he reported on academe and the sciences for the world's leading publications and sought out the best baths--or banyas--everywhere he went. His story of Russia through its cult of steam begins on a frosty Sunday morning in a gypsy cab traveling to a bathhouse in Moscow, where the steam is conjured by an out-of-work carpenter named Grisha, who takes on MacWilliams as a kind of apprentice, allowing him into an otherwise closed world through which MacWilliams could see himself, and Russia, with different eyes. The Russian bathers insist, only half-jokingly, that the American is a spy. Writing in a highly engaging style, MacWilliams travels the country to convey the breadth of banya culture and what it means to steam, a process that is at once a simple cleansing and a deep purification. It awakens the body and quiets the mind, generating waves of good feeling akin to an endorphin high. Each chapter of this splendid book is an episode--spanning from several hours to several days--from the Far North, Moscow, the Ural Mountains, the Solovetsky Islands, and a southern stretch of the Volga River. With Light Steam, the title is derived from the phrase used in banyas in lieu of goodbye, is the only book in English devoted to the banya and the only volume in any language to present Russia through the lens of its bath culture, the most Russian thing there is. General readers and scholars alike will be enchanted with this unforgettable portrait of a people and a millennia-spanning tradition.